Fabrication of chitosan membrane : the effetcs of different polyethylene glycol compositions on membrane performance in oily wastewater treatment - Siti Hashimah, Mohd Hanif (2008)
A membrane is a thin layer of material that is capable of separating materials as a function of their physical and chemical properties. It can be categorized by the driving forces employed which are microfiltration, ultrafiltration, nanofiltration and reverse osmosis. Ultrafiltration is chosen to do the treatment. Membrane technology has many advantages in treating wastewater such as simple efficient separating devices to restrain oil, grease, metal, BOD and COD. Besides this technology gain low energy cost and provide clear permeate which can be re-used. By considering public health and environmental awareness, biopolymer will be focus. Chitosan is chosen as it is a basic commercialized biopolymer that is prevailingly neutral or acidic. As in membrane separation process it occur fouling problem due to it retentate that attached to the membrane surface. For that chitosan will be crosslink with other polymer which is polyethylene glycol (PEG). PEG is good water permeability and chemically stabilizes to be applying as a membrane coating. Thus improve anti-fouling properties. The performance of this chitosan membrane in oily wastewater treatment is studied by varying different composition of PEG. The membrane morphology is obtained by scanning electron microscopy (SEM). The analysis is done by swelling the membrane in oily wastewater. From the analysis the result is get by seeing the percentage of oil that can be absorbed by the membrane of sample X, sample 1, sample 2 and sample 3. As the result sample 3 which consist with 3.6 gram of PEG is the best membrane. As the conclusion, PEG enhanced the performance of Chitosan membrane.